2014
DOI: 10.5194/acpd-14-8393-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mesoscopic surface roughness of ice crystals pervasive across a wide range of ice crystal conditions

Abstract: Abstract. Here we show high-magnification images of hexagonal ice crystals acquired by Environmental Scanning Electron Microscopy (ESEM). Most ice crystals were grown and sublimated in the water vapor environment of an FEI-Quanta-200 ESEM, but crystals grown in a laboratory diffusion chamber were also transferred intact and imaged via ESEM. All of these images display prominent mesoscopic topography including linear striations, ridges, islands, steps, peaks, pits, and crevasses; the roughness is not observed t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
17
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 55 publications
7
17
1
Order By: Relevance
“…In consequence, the HOP fraction is ∼ 0.01%, which is significantly smaller than measured by previous studies Chepfer, 2004, 2010]. Several papers have reported that surface texture of ice crystals may not be perfectly smooth [Magee et al, 2014], although a smooth surface is assumed in the hexagonal plates in this study due to limitation of PGOH computation. HOPs with a roughened surface may provide weaker backscattering intensity and higher depolarization ratio than those with a smooth surface, and therefore, this study could underestimate the plate and HOP fraction if clouds contain roughened plate particles.…”
Section: Global Statistics Of Plate Particlescontrasting
confidence: 54%
“…In consequence, the HOP fraction is ∼ 0.01%, which is significantly smaller than measured by previous studies Chepfer, 2004, 2010]. Several papers have reported that surface texture of ice crystals may not be perfectly smooth [Magee et al, 2014], although a smooth surface is assumed in the hexagonal plates in this study due to limitation of PGOH computation. HOPs with a roughened surface may provide weaker backscattering intensity and higher depolarization ratio than those with a smooth surface, and therefore, this study could underestimate the plate and HOP fraction if clouds contain roughened plate particles.…”
Section: Global Statistics Of Plate Particlescontrasting
confidence: 54%
“…3 panels, and Supplement 1). These observations of roughening are quite similar to those observed for ice particles grown within environmental SEM (Magee et al 2014;Pfalzgraff et al 2010;Neshyba et al 2013, Butterfield et al 2017 as well a new experimental growth chamber built specifically to investigate ice surface roughening (Voigtländer et al 2018). These observations of roughness at amplitudes and patterning agree with in-situ reports of multi-scale roughness by Collier et al 2016.…”
Section: Mesoscopic Roughening At Multiple Scales and Diverse Texturingsupporting
confidence: 82%
“…Indeed, recent years have seen considerable progress along these lines. In particular, investigations using scanning electron microscopy have shown that roughness can span multiple spatial scales [ Neshyba et al ., ; Magee et al ., ] and can be distinctly azimuthally anisotropic [ Pfalzgraff et al ., ].…”
Section: Introductionmentioning
confidence: 99%